Cellular selectivity and biological impact of cytotoxic rhodium(III) and iridium(III) complexes containing methyl-substituted phenanthroline ligands - Geldmacher, Yvonne; Kitanovic, Igor; Alborzinia, Hamed; Bergerhoff, Katharina; Rubbiani, Riccardo; Wefelmeier, Pascal; Prokop, Aram; Gust, Ronald; Ott, Ingo; Wölfl, Stefan; Sheldrick, William S. (ChemMedChem, 2011)
The antiproliferative properties and biological impact of octahedral iridium(III) complexes of the type fac-[IrCl3(DMSO)(pp)] containing pp=phenanthroline (1) and its 4- and 5-methyl (2, 3) and 4,7- and 5,6-dimethyl derivatives (4, 5) were investigated for both adherent and non-adherent cells. A series of similar rhodium(III) complexes were studied for comparison purposes. The antiproliferative activity toward MCF-7 cancer cells increases eightfold from IC50=4.6 for 1 to IC50=0.60 μM for 5, and an even more pronounced 18-fold improvement was established for the analogous rhodium complexes 6 and 8, the respective IC50 values for which are 1.1 and 0.06 μM. Annexin V/propidium iodide assays demonstrated that the 5,6-dimethylphenanthroline complexes 5 and 8 both cause significant inhibition of Jurkat leukemia cell proliferation and invoke extensive apoptosis but negligible necrosis. The percentages of Jurkat cells exhibiting high levels of reactive oxygen species correlate with the percentages of cells undergoing apoptosis. The antiproliferative activity of 5 and 8 is strongly selective toward MCF-7 and HT-29 cancer cells over normal HFF-1 and immortalized HEK-293 cells. Complex 5 also exhibits high selectivity toward BJAB lymphoma cells relative to healthy leukocytes. Both 5 and 8 invoke permanent decreases in the adhesion and respiration of MCF-7 cells.